Institutions, freedom, and technical efficiency - Adkins, Lee C.; Moomaw, Ronald L.; Savvides, Andreas (My University, 2002)
The impact of institutions on economic performance is currently the subject of much research. In this study we use panel data to estimate a stochastic production frontier and the sources of inefficiency for a broad set of countries. A maximum-likelihood procedure is used to estimate the parameters for the stochastic production frontier and the determinants of inefficiency simultaneously. Our results show that institutions that promote greater economic freedom in turn promote efficiency.